Experimental evaluation on well pattern adaptability of ultra-low permeability reservoir using sandstone flat model - Xiao, Qian-hua; Wei, Guo-qi; Yang, Zheng-ming; Xu, Xuan; Tian, Wen-bo; Zhang, Ya-pu (Journal of Central South University, 2014)
As for ultra-low permeability reservoir, the adaptability of common nine-spot well pattern is studied through large-scale flat models made by micro-fractured natural sandstone outcrops. Combined with non-linear porous flow characteristics, the concept of dimensionless pressure sweep efficiency and deliverability index are put forward to evaluate the physical models’ well pattern adaptability. Through experiments, the models’ pressure distribution is measured and on which basis, the pressure gradient fields are drawn and the porous flow regions of these models are divided into dead oil region, non-linear porous flow region, and quasi-linear porous flow region with the help of twin-core non-linear porous flow curve. The results indicate that rectangular well pattern in fracture reservoirs has the best adaptability, while the worst is inverted nine-spot equilateral well pattern. With the increase of drawdown pressure, dead oil region decreases, pressure sweep efficiency and deliverability index increase; meantime, the deliverability index of rectangular well pattern has much more rational increase. Under the same drawdown pressure, the rectangular well pattern has the largest pressure sweep efficiency.